Psychology and law in Europe: when West meets East - Shaboltas, Alla (CRC Press, Taylor & Francis Group, 2017)
Forensic and criminal psychology in Russia : history of development and current state / A. Shaboltas -- Legal consciousness : the nervous chord of a legal system / Djenevra I. Lukovskaya and Maria A. Kapustina -- The origin of the paternalistic tradition in Russian social consciousness / Marina Igorevna Yudina -- Lay thinking about 'sexual murderer' and 'victim' in groups of young Russian men and women / Nikolay Dvoryanchikov, Inna Bovina, Olga Logunova and Anastasiya Gutnick -- Assumptions underlying behavioral linkage revisited : ascertaining individual differentiation and consistency in serial rape / Marina Sorochinski and C.Gabrielle Salfati -- Victims or "fighters"? Narratives of abused women who killed their male intimate partners / Paula Sismeiro Pereira -- Mock jurors' understanding of forensic science and its perceived importance in judicial processes / Laura Hammond and Maria Ioannou -- Dysfunctional economic behaviour : victims of financial debt (the case of microfinance organization clients) / Olga Deyneka -- Problem personalities in the workplace : development of the corporate personality inventory / K. Fritzon, C. Bailey, S. Croom and N. Brooks -- How moral emotions affect the probability of relapse / André Körner, Rose Schindler and Tina Hahnemann -- Personality traits of juveniles convicted of sexual assault / Gayane A. Vartanyan and Sergey V. Gorbatov -- Risk-taking behaviour, values, and attitudes towards traffic safety among street racers in St. Petersburg / J. V. Granskaya and V. A. Zaicev -- The eye-closure interview : the practical utility of instructing eyewitnesses to close their eyes / Annelies Vredeveldt and Colin G. Tredoux -- Understanding false memories : dominant scientific theories and explanatory mechanisms / Julia Shaw -- Verbal lie detection / Aldert Vrij and Galit Nahari